1/10=x hope that helps a bunch
You've written "then" before 3, so i assume the real question is:
(40 * 40 * 40 + 26 - 98 + 45 * 78 * 78 * 78) / 3
Use "PEMDAS" first solve under the parenthesis, then after it.
= (64000 + 26 - 98 + 21354840) / 3
= 21418768 / 3
= 7139589.33
In short, Your Answer would be: 7139589.33
Hope this helps!
Answer:
(f - g)(x) = -x² + 3x + 5
General Formulas and Concepts:
<u>Pre-Algebra</u>
<u>Algebra I</u>
- Function Notation
- Combining Like Terms
Step-by-step explanation:
<u>Step 1: Define</u>
f(x) = 3x + 5
g(x) = x²
(f - g)(x) is f(x) - g(x)
<u>Step 2: Find (f - g)(x)</u>
- Substitute: (f - g)(x) = 3x + 5 - x²
- Rewrite: (f - g)(x) = -x² + 3x + 5
Answer:
one inch on the map is 8 miles
Step-by-step explanation:
divide 24 by 3